Integrasi Agama dan Sains Dalam Perspektif Seyyed Hossein Nasr - M, Amril; Fitri, Anisa; Dewi, Eva; Hidayati, Okfrida (Peneliti.net, 2025)
The purpose of this article is to discuss the integration of religion and science in the perspective of Seyyed Hossein Nasr. The urgency of this study is to know and understand how the integration of religion and science in the perspective of Seyyed Hossein Nasr. The results of the study concluded that Sayyed Hossein Nasr, a Muslim intellectual, provided an alternative view of the relationship between religion and science. He criticized the secular approach in modern science that ignores the spiritual dimension of man. Instead, Nasr proposed the concept of scientia sacra that integrates science with spirituality. This concept is supported by the principle of unitas (the unity of all things) and cosmic hierarchy (the relationship between god, man, and nature). By studying the history of science in Islam, Nasr shows that the integration of religion and science is not new. However, he also criticized the secularization of modern science that has eliminated the spiritual dimension. Nasr's thinking has far-reaching implications, especially in education and in dealing with contemporary challenges such as environmental and ethical issues.